End of „Mass Imprisonmet” Policy in the USA? (Un)profitability Widespread Use of Inprisonment - Kamil Miszewski (Polish Journal of Social Rehabilitation, 2016)
Since the 1970s, the number of prisoners in the US has been increasing., but this is not due to an increase in crime as statistics during this time actually indicate a decline. America is living with the illusion that imprisonment is the cure for crime. The majority of funds from the budget, rather than being spent on education, welfare and health, goes to gigantic expansions of prisons. Legislation under which an increasing number of criminals is sentenced to longer terms of imprisonment for an even broader range of offenses has changed. Support for such a number of new prisoners consumes more and more costs, both financial and social. This realization came quite late, because only in 2011, when the financial system of California, a state which expanded its prison system the most of all the US states, broke down. Since then, the prison population of the United States has begun to decrease slightly.